Churchill's folly : how Winston Churchill created modern Iraq - Catherwood, Christopher (New York : Carroll & Graf Pub., 2004)
A scholar and adviser to Tony Blair's government analyzes how Churchill created the artificial monarchy of Iraq after World War I, thereby forcing together unfriendly peoples under a single ruler. Using T.E. Lawrence to induce Arabs under the rule of the Ottoman Turks to rebel against their oppressors, the British and French during World War I convinced the Hashemite clan that they would rule over Syria. In fact, Britain had promised the territory to the French. To make amends, Churchill created the nation of Iraq and made the Hashemite leader, Feisal, king of a land to which he had no connections at all. Defying a global wave of nationalistic sentiment, and the desire of subject peoples to rule themselves, Churchill created a Middle Eastern powder keg.--Publisher description.
Includes bibliographical references and index.
Keywords: Churchill, Winston, -- 1874-1965.; Iraq -- Relations -- Great Britain; Iraq -- History -- 1921-